PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KEJELASAN SASARAN ANGGARAN, AKUNTABILITAS PUBLIK, EVALUASI ANGGARAN TERHADAP KINERJA APARAT PEMERINTAH DAERAH (SKPD KABUPATEN KAMPAR) - Ning Umbar Susilowati; Andreas '; Devi Safitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aims to examine the effect of budgeting participation, budget goal clarity, public accountability, and budget evaluation on performance of local government officials (SKPD Kampar District). Respondents of this study are the government officials who work in kampar district. A totals of 128 questionnaire were distributed to the respondents and 116 questionnaire were returned for analysis. Data analysis method is using multiple linear regression. The result revealed that budgeting participation, budget goal clarity, public accountability, and budget evaluation has influence on performance of local government officials.Keywords: budgeting participation, budget goal clarity, public accountability, budget evaluation, and performance officials